Profitability management of agricultural enterprises in Ukraine - Iryna Oleksandrenko; Viktoria Valchyshyna (Економічний форум)
The article presents theoretical aspects of profitability management of agricultural enterprises, taking into account the main modern conditions of their functioning. The purpose of this study is to substantiate the need to manage the profitability of agricultural enterprises and to identify the main structural elements of the mechanism of this management process. As a result of studying different approaches to the interpretation of profitability, it is determined that profitability is a generalizing relative indicator of performance, which makes it possible to assess the amount of profit for each hryvnia invested in the work of an economic entity and acts as an indicator of its stable and successful functioning. Based on the formed definition of profitability, its key characteristics are systematized, which are reduced to its impact on the activities of any business entity. The main factors of influence on the profitability of agricultural enterprises are identified and systematized, the consideration of which will allow to form effective management decisions and achieve the set goals. The necessity of managing the profitability of agricultural enterprises is substantiated and its essence is determined, which allowed to form the main structural elements of the mechanism for implementing this process. The article reflects the main principles of profitability management of agricultural enterprises, compliance with which will allow these business entities to effectively carry out management tasks. The main types of management of profitability of agricultural enterprises are studied in detail, which are reduced to the availability of software and hardware, regulatory, resource and accounting and analytical support. The key methods, tools and levers of the management process aimed at increasing the profitability of agricultural enterprises are presented. As a result of theoretical research, the directions of achieving a high level of profitability of agricultural enterprises are identified and presented, which are mainly reduced to reducing production costs and improving the efficiency of credit and marketing policy of agricultural producers. The results obtained during the writing of the article can be practically used in the activities of any agricultural enterprise, the purpose of which is to find alternative ways to increase profits and increase profitability in today's difficult economic conditions